Electrical and Structural Characterization of Thin Pb0.5S0.5 Films Deposited with Different Thicknesses - Abdullah, Rasha A (Al-Nahrain Journal of Science, 2018)
Pb0.5S0.5 alloy has been prepared successfully by the method of quenching for elements melt. The Pb0.5S0.5 thin films of 200, 400, 600, 800 and 1000 nm thickness have been prepared from the prepared alloys by thermal evaporation technique onto glass substrate at room temperatures. The X-ray diffraction study shows that the prepared films are cubic polycrystalline structure with strong peaks at (200) and (111) planes, the intensity of the peaks increases with increasing film thickness. The grain size increases with increasing film thickness and their values varied between 35 and 59 nm. The D.C conductivity has been displayed two stages of conductivity through the whole temperature range. D.C conductivity have increased from 0.50×10-2 to 1.86×10-2 (Ω.cm)-1 as film thickness increased. All prepared films have two activation energies, where these values decrease with increasing thickness. The maximum value of activation energy was 0.177eV at 200nm thickness, and then decreased to 0.067 eV in thermal range 413-493K. Hall Effect results have been shown that all prepared thin Pb0.5S0.5films were p-type material. The carrier concentration increases with increasing thickness, and it varies from 0.079×1019 cm-3 to 9.55×1019 cm-3 for thickness from 200 to 1000nm. The Hall mobility has been decreased from 3.99 to 0.098 (cm2/V.sec) as thickness increased from 200 to 1000nm. The drift velocity of these films decreases with increasing this films thickness.